Transnational Crime of Illicit Drugs in Southeast Asia - Harza, Zulkifli (Andalas Institute of International Studies UNAND, 2023)
The cooperation of the actors in harmonizing their views on the drug phenomenon is needed. Over the last decade, the dynamics that define the regional security environment in Southeast Asia have changed dramatically. In this study, a descriptive qualitative methodological approach was adopted to explore an in-depth understanding of cross-border crime in the illegal drug trade in Southeast Asia. The conclusions of this analysis will help enrich our understanding of cross-border illegal drug transactions in the region, as well as provide a basis for formulating better policy recommendations to effectively address this challenge. ASEAN needs to strengthen its commitment of cooperation and continuously make efforts were tireless in the fight against drugs.